Ductal Carcinoma In Situ Arising in Sentinel Axillary Lymph Nodes Excised From Patients With Breast Carcinoma - A Potential Diagnostic Pitfall. Report of Two Cases - Aysel Bayram; Ali Yılmaz Altay; Sidar Bağbudar; Semen Önder; Mustafa Tükenmez; Ekrem Yavuz (European Journal of Breast Health, 2023)

(untitled)
We present two cases of ductal carcinoma in situ (DCIS) that arose in axillary lymph nodes excised as the sentinel lymph node from two patients with breast carcinoma. The patient ages were 72 and 36 years and both patients underwent mastectomy and axillary lymph node dissection. In addition to DCIS in the sentinel lymph node, the first patient had a wide DCIS and microinvasion in the ipsilateral breast and a micrometastasis in another sentinel lymph node. The second patient was operated on after neoadjuvant chemotherapy and had DCIS and a small focus of invasion, in addition to invasive and in situ ductal carcinoma in the lymph node having signs of chemotherapy-induced regression. The presence of DCIS was confirmed by use of the immunohistochemical method with antibodies against myoepithelial cells. As a potential source of cellular origin, DCIS was accompanied by benign epithelial cell clusters in the lymph node in both cases. Morphologic and immunohistochemical features were similar in breast and lymph node neoplasms. We conclude that DCIS may rarely develop from benign epithelial inclusions in the axillary lymph node and is a potential diagnostic pitfall in cases having ipsilateral breast carcinoma.